Pembuatan Indeks Beranotasi Jurnal Statistik Ekonomi Keuangan Daerah Sumatera Barat Tahun 2015 di Perpustakaan Kantor Perwakilan Bank Indonesia Provinsi Sumatera Barat - Gustari, Elvira; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discusses the making of statistical journal annotated index of financial economics at the Library of West Sumatra Indonesia Bank Office of West Sumatra Province. This paper aims to describe the manufacturing index statistics annotated journals of Financial Economics West Sumatra to make it easier to find back the information needed at any time. Data analysis used descriptive method. Data were collected through observation or direct research at the Library of Bank Indonesia Representative Office of West Sumatra Province. From the analysis of data through observation and direct research, collected a total of 12 collections. Based on analyzing the data, it can be concluded that the measures in the manufacturing index annotated as follows: (a) the initial observation of the collection; (b) the selection of the collection will be indexed; (c) recording the description of the collection; (d) creation of annotations; (e) determine the keywords; (f) index creation; (g) the preparation of the index; (h) typing index.Â Keyword: Index, film, statistical, enonomics.